COMPETITIVENESS OF AN INNOVATIVE CUTTING MECHANISM FOR UNLOADING SILAGE FROM TRENCH STORAGES - RUTKEVYCH, VOLODYMYR; SPIRIN, ANATOLII; OSTAPENKO, ALEXEI (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The problem of increasing the efficiency of unloading stem fodder from trench storages, which is one of the key stages in the technology of procurement and storage of fodder for livestock farming, is considered. The feasibility of using a cutting mechanism for unloading silage, the design feature of which is the use of a hydraulic drive, is substantiated. The special role in the functioning of the hydraulic drive of the cutting mechanism of the throttle flow divider with a compensation rod is noted, which ensures synchronization of the work of the executive bodies, uniform distribution of the working fluid and stability of the drive parameters. The principle of operation of the flow divider is based on balancing the flow of the working fluid in parallel hydraulic lines, which allows you to automatically equalize the load between the hydraulic motors and prevent their asynchronous operation. The methodology for assessing the competitiveness of the developed mechanism is outlined on the basis of dimensionless and generalizing indicators of the 1st and 2nd types, which reflect the level of technical perfection and functional efficiency. According to the results of calculations, it was established that the proposed design is characterized by the highest values of dimensionless indicators: 0.7464 (type I) and 4.7235 (type II), which confirms its superiority over existing analogues. The obtained rating, in which the studied mechanism takes first place, testifies to its competitiveness and feasibility of practical application. The high level of productivity, reliability and quality of silage unloading operations is explained by the optimal combination of design and technological solutions. Promising directions for further research are indicated: experimental tests in production conditions, studying the influence of the operating parameters of the hydraulic drive on the quality of work, optimization of the cutting mechanism taking into account energy consumption and wear resistance, development of an automated process control system and assessment of the economic efficiency of implementation.
Keywords: cutting mechanism; stem feed; working body; hydraulic pump; hydraulic motor; hydraulic drive; flow divider